Shariah disclosure expectation gap between Shariah practitioners and Islamic banks’ customers in Malaysia - Md Amin, Nur Afiqah; Mohd Ariffin, Noraini; Fatima, A.H. (Asian Journal of Accounting Perspectives, 2021)
Research aim: The aim of this study is to examine the possibility of a gap in perception between Shariah practitioners and customers of Islamic banks on the importance of Shariah disclosure by Islamic banks. Design/ Methodology: Questionnaires were distributed to Shariah practitioners, consisting of Shariah committee members and Shariah officers, and Islamic banks’ customers who were lecturers and final year accounting students. The concept of expectation gap derived from the auditing literature was extended and applied to this study’s context. A total of 64 and 200 questionnaires were distributed to Shariah practitioners and customers of Islamic banks, respectively. The response rates were 41% for Shariah practitioners and 65% for Islamic banks’ customers. Research findings: The results indicate that Shariah practitioners and customers perceive all Shariah disclosure items as important to be disclosed. However, a few significant differences were noted between both groups, suggesting the existence of an expectation gap, albeit minimal. Only a minimal gap between the selected customers and practitioners may be reasonable, as the group of customers consisted of informed customers. Theoretical contribution/ Originality: This study contributes to knowledge as there is a dearth of literature that determines customers’ perceptions of Shariah disclosure. Practitioner/ Policy Implications: The results provide regulators and Islamic banks with valuable insight into the importance of Shariah disclosure items from the points of view of customers and Shariah practitioners on which items they concur as important and which items they differ in opinion. Limitation/ Implication: This study is an initial effort to examine the expectation gap between knowledgeable customers and Shariah practitioners on the Shariah disclosure made by Islamic banks. The customers are respondents from only one university; hence, there is a limitation concerning the generalisability of the findings. Thus, future research could extend such an investigation to other customers in order to enhance generalizability. Keywords: Expectation Gap, Shariah Disclosure, Islamic Banks Type of article: Research paper JEL Classification: G21, M41, N25